2022
DOI: 10.1108/jkm-05-2022-0421
|View full text |Cite
|
Sign up to set email alerts
|

Sharing or hiding? The influence of supervisor bottom-line mentality on employee knowledge behaviors

Abstract: Purpose Drawing on the dual-strategies theory of social rank and leader distance theory, this paper aims to investigate the influence of supervisor bottom-line mentality (BLM) on employee knowledge-related behaviors by considering the mediating role of perceived leader prestige or dominance and the moderating role of supervisor–subordinate guanxi (SSG). Design/methodology/approach This study collected survey data from 185 research and development employees in East China at three-time points. The authors cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…We included all items simultaneously for factor analysis, and the results showed that the cumulative variance interpretation rate of the single-factor was 25.19%, far less than the standard of 40%. Second, we added a common method factor to form a five-factor model on top of the four-factor model, and the result of the five-factor model could not be fitted in Mplus software, which again indicated that there was no serious common method bias in this study (Chen et al ., 2022; Liu et al ., 2022).…”
Section: Study 1 Field Study: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We included all items simultaneously for factor analysis, and the results showed that the cumulative variance interpretation rate of the single-factor was 25.19%, far less than the standard of 40%. Second, we added a common method factor to form a five-factor model on top of the four-factor model, and the result of the five-factor model could not be fitted in Mplus software, which again indicated that there was no serious common method bias in this study (Chen et al ., 2022; Liu et al ., 2022).…”
Section: Study 1 Field Study: Resultsmentioning
confidence: 90%
“…five-factor model could not be fitted in Mplus software, which again indicated that there was no serious common method bias in this study (Chen et al, 2022;Liu et al, 2022).…”
Section: Authentic Leadership and Resistance To Changementioning
confidence: 82%
“…The reason why we choose R&D companies is that they have high requirements on employees’ knowledge and skills. On the one hand, the employees in R&D companies are more likely to have relative perceived qualification, and on the other hand, R&D companies also provides soil for knowledge seeking and knowledge sabotage (Chen et al , 2022; Li et al , 2022). First, we communicated the research purpose (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…First, we conducted a reliability test on the scale and referred to a paper published in the authoritative journal "Journal of Knowledge Management" (Chen et al, 2022) to calculate Cronbach's a And CR (composite reliability). The Cronbach's a of the main five constructs (Workplace ostracism, anger, knowledge sabotage behavior, employee BLM and conscientiousness) were 0.936, 0.882, 0.906, 0.848 and 0.745 in order and each of them exceeded 0.7, indicating that the reliability of each scale was good.…”
Section: Preliminary Analysismentioning
confidence: 99%
“…Through the translation back translation process (Brislin, 1970) and multiple rounds of review by professors and professional translators when preparing and finalizing the questionnaire, the surface validity and content validity of the measurement scale were ensured (Perotti et al, 2023). On the other hand, referring to the research by Chen et al (2022) and Wang et al (2022), we used confirmation factor analysis to test the discriminant validity between the main five constructions (Table 1). The results show that the fitting degree of the five-factor model (x 2 ¼ 699.150, df ¼ 314, x 2 /df ¼ 2.227, incremental fit index (IFI) ¼ 0.914, Tucker-Lewis index (TLI) ¼ 0.904, comparative fit index (CFI) ¼ 0.914, RSMEA ¼ 0.054) was significantly superior to that of other models, demonstrating that the five variables had high discriminant validity.…”
Section: Preliminary Analysismentioning
confidence: 99%